2007
DOI: 10.1016/j.ejphar.2006.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Bis-imide granulatimide analogues as potent Checkpoint 1 kinase inhibitors

Abstract: Granulatimide and isogranulatimide, natural products isolated from an ascidian, were found to be abrogators of the cell cycle G2-M phase checkpoint by inhibition of Checkpoint 1 kinase (Chk1). In the course of structure-activity relationship studies on granulatimide analogues, we have synthesized a series of bis-imides, in which the imidazole moiety was replaced by an imide heterocycle. Various modifications have been introduced on one or both imide heterocycles, on the benzene ring, and on the indole nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Chk1 was predicted to be a target of granulatimides chemical family (Roberge et al, 1998); which we and others have confirmed (Henon et al, 2008;Henon et al, 2007;Jiang et al, 2004). Isogranulatimide is a natural compound from the ascidian Didemnum granulatum (Roberge et al, 1998).…”
Section: Chk1 Inhibitors and Their Propertiessupporting
confidence: 84%
See 2 more Smart Citations
“…Chk1 was predicted to be a target of granulatimides chemical family (Roberge et al, 1998); which we and others have confirmed (Henon et al, 2008;Henon et al, 2007;Jiang et al, 2004). Isogranulatimide is a natural compound from the ascidian Didemnum granulatum (Roberge et al, 1998).…”
Section: Chk1 Inhibitors and Their Propertiessupporting
confidence: 84%
“…S29285 is a bisimide derivative of isogranulatimide and the S29859 is a chlorinated derivative containing a pyrrole ring. S29285 was neither cytotoxic (Henon et al, 2007) or active in the checkpoint bypass assay. We subsequently found that this compound was unstable in aqueous solutions.…”
Section: Chk1 Inhibitors and Their Propertiesmentioning
confidence: 93%
See 1 more Smart Citation
“…10 Some isoindole-1,3-dione derivatives are active in reducing the growth of colon adenocarcinoma, osteosarcoma, and KB nasopharynx. 11 Isoindole-1,3-diones are also known for their antiviral, 12 antiinflammatory, 13 Chk1 inhibitory, 14 sedative, 15 bactericidal, and fungicidal 16 properties. They also find important applications as synthetic intermediates in the dye, 17 pesticide, 18 and polymer 19 industries.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the photophysical and chemical properties, organic imides and diimides also play significant role in pharmacology. Imides possess wide range of biological activities such as antiinflammatory (21Á24), anticancer (25,26), antimicrobial (27), DNA binding, and apoptotic-inducing activities (28), etc. They also act as selective a1d-adrenergic receptor antagonists which modulate intercellular biochemical processes in response to changes in extracellular concentrations of the neurotransmitter norepinephrine and the circulating hormone epinephrine, leading to widespread physiological actions that make them attractive targets for *Corresponding author.…”
mentioning
confidence: 99%